Lack of Effects of a Single High-Fat Meal Enriched with Vegetable n-3 or a Combination of Vegetable and Marine n-3 Fatty Acids on Intestinal Peptide Release and Adipokines in Healthy Female Subjects - Narverud, Ingunn; Myhrstad, Mari C. W.; Herzig, Karl-Heinz; Karhu, Toni; Dahl, Tuva B.; Halvorsen, Bente; Ulven, Stine M.; Holven, Kirsten B. (Frontiers in Nutrition, 2016)
Peptides released from the small intestine and colon regulate short-term food intake by suppressing appetite and inducing satiety. Intake of marine omega-3 (n-3) fatty acids from fish and fish oils is associated with beneficial health effects, whereas the relation between intake of the vegetable n-3 fatty acid α-linolenic acid and diseases is less clear. The aim of the present study was to investigate the postprandial effects of a single high-fat meal enriched with vegetable n-3 or a combination of vegetable and marine n-3 fatty acids with their different unsaturated fatty acid composition on intestinal peptide release and the adipose tissue. Fourteen healthy lean females consumed three test meals with different fat quality in a fixed order. The test meal consisted of three cakes enriched with coconut fat, linseed oil and a combination of linseed and cod liver oil. The test days were separated by two weeks. Fasting and postprandial blood samples at three and six hours after intake were analysed. A significant postprandial effect was observed for cholecystokinin, peptide YY, glucose-dependent insulinotropic polypeptide, amylin and insulin which increased, while leptin decreased postprandially independent of the fat composition in the high-fat meal. In conclusion, in healthy, young, lean females, an intake of a high-fat meal enriched with n-3 fatty acids from different origin stimulates intestinal peptide release without any difference between the different fat compositions.